Perbedaan Kadar Hemoglobin pada Ibu Hamil dengan Preeklamsi Ringan, Berat, dan Eklamsi di Rumah Sakit Umum Daerah (RSUD) Ciawi - Ajeng Normala; Fernando Nathaniel; Dean Ascha Wijaya; William Gilbert Satyanegara (Lembaga Pengembangan Kinerja Dosen, 2023)
Measurement of haemoglobin (Hb) is a standard examination in pregnant women at the first prenatal visit that is used to evaluate physical status and anemia. One of the health conditions that often occurs and is important to note in reducing maternal and perinatal morbidity and mortality is anemia in pregnancy, which can increase the risk of infection, preeclampsia, postpartum hemorrhage, low birth weight babies, preterm birth, to death for both mother and child. fetus. This cross-sectional study aims to determine the difference in mean haemoglobin levels with the incidence of mild preeclampsia, severe preeclampsia and eclampsia which were selected according to the criteria by total sampling using medical record data in the period January 2020 - December 2020. The variables in this study consisted of the basic characteristics of the respondents (age mother and parity status), gestational age (weeks), and medical condition of the mother divided into three groups (mild, severe preeclampsia, and eclampsia). Statistical analysis using the Kruskall Wallis test. This study included 190 respondents with an average maternal age of 32 years and an average haemoglobin level of 10.86 with medical conditions dominated by severe preeclampsia (85.3%). The results of the study found that there was no significant difference in mean hemoglobin levels between the three groups of pregnant women (p-value: 0.235). To improve the quality of life of the mother and fetus, it is recommended that primary health services should be strengthened, prevention, early diagnosis and treatment of anemia in pregnancy should be prioritized.